Ω‐Imidazolyl‐alkyl derivatives as new preclinical drug candidates for treating non‐alcoholic steatohepatitis. Issue 6 (26th March 2021) - Diesinger, Torsten; Lautwein, Alfred; Buko, Vyacheslav; Belonovskaya, Elena; Lukivskaya, Oksana; Naruta, Elena; Kirko, Siarhei; Andreev, Viktor; Dvorsky, Radovan; Buckert, Dominik; Bergler, Sebastian; Renz, Christian; et al.
Abstract: Cytochrome P450 2E1 (CYP2E1)‐associated reactive oxygen species production plays an important role in the development and progression of inflammatory liver diseases such as alcoholic steatohepatitis. We developed two new inhibitors for this isoenzyme, namely 12‐imidazolyl‐1‐dodecanol (I‐ol) and 1‐imidazolyldodecane (I‐an), and aimed to test their effects on non‐alcoholic steatohepatitis (NASH). The fat‐rich and CYP2E1 inducing Lieber‐DeCarli diet was administered over 16 weeks of the experimental period to induce the disease in a rat model, and the experimental substances were administered simultaneously over the last four weeks. The high‐fat diet (HFD) pathologically altered the balance of reactive oxygen species and raised the activities of the liver enzymes alanine aminotransferase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (AP) and γ‐glutamyl‐transferase (γ‐GT); lowered the level of adiponectine and raised the one of tumor necrosis factor (TNF)‐α; increased the hepatic triglyceride and phospholipid content and diminished the serum HDL cholesterol concentration. Together with the histological findings, we concluded that the diet led to the development of NASH. I‐ol and, to a lesser extent, I‐an shifted the pathological values toward the normal range, despite the continued administration of the noxious agent (HFD). The hepatoprotective drug ursodeoxycholic acid (UDCA), which is used off‐label in clinical practice, showed a lower effectiveness overall. I‐ol, in particular, showed extremely good tolerability during the acute toxicity study in rats. Therefore, cytochrome P450 2E1 may be considered a suitable drug target, with I‐ol and I‐an being promising drug candidates for the treatment of NASH. Abstract : We developed two new inhibitors of Cytochrome P450 2E1 (CYP2E1), namely 12‐imidazolyl‐1‐dodecanol (I‐ol) and 1‐imidazolyldodecane (I‐an), to reduce the reactive oxygen species (ROS) production and aimed to test their effects on non‐alcoholic steatohepatitis (NASH). Our findings suggest that CYP2E1 may be considered a suitable drug target, with I‐ol and I‐an being promising drug candidates for the treatment of NASH.